Gamify Your Classroom - Lankshear, Colin,Knobel, Michele,Farber, Matthew (Peter Lang Inc., 2018)
This completely revised and expanded field guide is packed with new innovative ideas on how to implement game-based learning and gamification techniques in everyday teaching. With nearly two dozen more experts than the first edition, this book contains interviews with more than 70 authorities in the field, including academics such as James Paul Gee, Kurt Squire, Mizuko (Mimi) Ito, Lee Sheldon, Jordan Shapiro, and Mary Flanagan. The author also shares conversations with experts from numerous organizations such as Common Sense Media, iCivics, DragonBox, Connected Camps, GlassLab Games, Schell Games, Institute of Play, Games for Change, BrainPOP, Tiggly, Toca Boca, ThinkFun, BrainQuake, Filament Games, BreakoutEDU, Kahoot, Classcraft, and more. Featuring a new introduction, as well as a foreword from USA Today’s national K-12 education writer Greg Toppo, this book provides new practical lesson plan ideas, ready-to-use games, and links for further research in each updated chapter. Included are best practice recommendations from star game-based learning teachers, including Steve Isaacs, Peggy Sheehy, Michael Matera, Rafranz Davis, Zack Gilbert, and Paul Darvasi. Regardless of your teaching discipline or grade level, whether you are new to game-based learning or if you have experience and want to take a deeper dive, this book will engage and reinvigorate the way you teach and how your students learn!...
10.3726/978-1-4331-3882-9
Keywords: Lernspiel; Unterrichtsmethode; Lernerfolg; Computerspiel; Videospiel